ISLAMIC EDUCATION FOR SEA MULTICULTURAL SOCIETY - Raihani Raihani (Asia-Pacific Journal on Religion and Society, 2022)
Religious education in schools in many of Southeast Asian countries is compulsory. In the Malay-Muslim majority countries, Islamic education like other religions education is a must, and the governments mandate and support it fully as part of the national education system. Islamic education is, however, often described in media as a hotbed for radicalization. Although most of this description is not valid, the tendency of some Islamic schools to become less moderate and less tolerant has been evident by the growing numbers of schools which are influenced by radical ideologies of Islam such as Salafism. Based on analysis of Islamic education practices in some SEA countries and Grimmit’s theory of religious education, this paper proposes a model of Islamic education which may be useful in shaping the Islamic religion classes to respond to challenges of religious and cultural diversity. This model is an initial thought of how to design a more humanist religion class, therefore, open for further debates and refinements